Partial loss of USP9X function leads to a male neurodevelopmental and behavioral disorder converging on transforming growth factor beta signaling - Johnson, Brett; Dikow, Nicola (Biological psychiatry, 2020)
BACKGROUND: The X-chromosome gene USP9X encodes a deubiquitylating enzyme that has been associated with neurodevelopmental disorders primarily in female subjects. USP9X escapes X inactivation, and in female subjects de novo heterozygous copy number loss or truncating mutations cause haploinsufficiency culminating in a recognizable syndrome with intellectual disability and signature brain and congenital abnormalities. In contrast, the involvement of USP9X in male neurodevelopmental disorders remains tentative. METHODS: We used clinically recommended guidelines to collect and interrogate the pathogenicity of 44 USP9X variants associated with neurodevelopmental disorders in males. Functional studies in patient-derived cell lines and mice were used to determine mechanisms of pathology. RESULTS: Twelve missense variants showed strong evidence of pathogenicity. We define a characteristic phenotype of the central nervous system (white matter disturbances, thin corpus callosum, and widened ventricles); global delay with significant alteration of speech, language, and behavior; hypotonia; joint hypermobility; visual system defects; and other common congenital and dysmorphic features. Comparison of in silico and phenotypical features align additional variants of unknown significance with likely pathogenicity. In support of partial loss-of-function mechanisms, using patient-derived cell lines, we show loss of only specific USP9X substrates that regulate neurodevelopmental signaling pathways and a united defect in transforming growth factor signaling. In addition, we find correlates of the male phenotype in Usp9x brain-specific knockout mice, and further resolve loss of hippocannpal-dependent learning and memory. CONCLUSIONS: Our data demonstrate the involvement of USP9X variants in a distinctive neurodevelopmental and behavioral syndrome in male subjects and identify plausible mechanisms of pathogenesis centered on disrupted transforming growth factor beta signaling and hippocampal function.